Concerns on the human genoma - Ascenzo Cabello, Jorge (2015)
The development of science in the last century, is unparalleled in its evolution with the past, especially the biomedical sciences, which have caused such progress in the last thirty years, they have produced many ethical dilemmas causing instability and fear . This arises in society against the enormous power of biomedicine, with deterioration of ethical paradigms of reference in our Western culture.